The critique of everyday life. Adorno, Benjamin and the tasks of aesthetic praxis - Vitali, Rolando (Scenari, 2022)
In capitalist consumerist societies, the commodity form structurally mediates the everyday life. The reification performed by the commodity conceals the social relation through its sensible, aesthetical thing-like form and impedes the possibility to experience society as such. The critique of everyday life both in Benjamin and in Adorno aims to reactivate this possibility. Yet, their strategy radically differs: whereas Benjamin sees a possibility in the sensible re-appropriation of the technological apparatus, Adorno insists that only within the autonomous space of aesthetic autonomy of the work of art it is possible to experience society in its contradictory essence.